Development of information technology for analyzing the customer churn of a telecommunication company - Andrii Papa (Technology Audit and Production Reserves, 2022)
The object of research is the process of analyzing the customer churn of telecommunications companies based on machine learning methods. The existing problem is that, until recently, the process of customer churn was compensated by attracting new customers, but in the modern world, growth rates are constantly accelerating, the market is filled with a large number of competitors, which leads to a constant increase in customer requirements for products and services. In this regard, the process of attracting new customers becomes more costly and time-consuming, which in turn enhances the importance of maintaining an existing customer base.